Tiny House – when size matters. Issue 3 (2nd October 2018) - Wotton, Joshua; Skates, Henry; Shutter, Leigh
ABSTRACT: At 231 m 2, Australia has the largest average house size in the world. For many reasons, this is unsustainable. Tiny Houses (dwellings less than 37.2 m 2 ) are at the opposite end of the spectrum of house size. It is well understood that smaller houses use less materials than larger houses, less energy in their construction and use, and it can be argued that they produce less waste. Thus, a Tiny House is generally seen as being more sustainable than the average Australian house. However, the exaggerated reduction of size and function in some Tiny Houses means that they can end up being unliveable for many people in Australia. In contrast, Tiny Houses are the norm in many other countries. This suggests that there are many elements of choice in Australian housing that are considered a necessity. This paper investigates house size and elements of necessity and choice. It argues that to be sustainable we need to reconsider housing options. Tiny Houses could become a much larger proportion of housing stock, but the definition, understanding, design and production of the Tiny House needs to move beyond just achieving a prescribed floor area, to including the functional and amenity needs of the household occupants.